Attenuation mechanism of Brucella melitensis M5-10, implications for vaccine development and differential diagnosis - Yuanqiang ZHENG,Yanchun SHI,Chang AN,Ruisheng LI,Dongjun LIU,Yuehua KE,Kairong MAO,Mingjuan YANG,Zeliang CHEN,Shorgan BOU (Frontiers of Agricultural Science and Engineering, 2014)
Brucellosis is a worldwide zoonosis. Vaccination is the most efficient means to prevent and control brucellosis. The current licensed attenuated vaccines for animal use were developed by sequential passage in non-natural hosts that decreased virulence in its original hosts. The attenuation mechanism of these strains remains largely unknown. In the present study, we sequenced the genome of Brucella melitensis vaccine strain M5-10. Sequence analysis showed that a large number of genetic changes occurred in the vaccine strains. A total of 2854 genetic polymorphic sites, including 2548 SNP, 241 INDEL and 65 MNV were identified. Of the 2074 SNPs in coding regions, 1310 (63.2%) were non-synonymous SNPs. Gene number, percent and N/S ratios were disproportionally distributed among the cog categories. Genetic polymorphic sites were identified in genes of the virB operon, flagella synthesis, and virulence regulating systems. These data indicate that changes in some cog categories and virulence genes might result in the attenuation. These attenuation mechanisms also have implications for screening and development of new vaccine strains. The genetic changes in the genome represent candidate sites for differential diagnosis between these vaccine strains and other virulence ones. Transcription analysis of virulence genes showed that expression of dnaK, vjbR were reduced in M5-10 strain when compared with that in 16M. A duplex PCR targeting virB6 and dnaK was successfully used to differentiate between M5-10 and the virulent 16M strain. The genome re-sequencing technique represents a strong strategy not only for evaluation of vaccines, but also for development of new vaccines.